Naturally occurring prenylated coumarins from Micromelum integerrimum twigs - Phakhodee W. (Elsevier BV, 2014)
A phytochemical investigation of secondary metabolites from Micromelum integerrimum was reported. Two new prenylated coumarins named as hydramicromelin D (1) and integerrimelin (2) were isolated along with 9 known coumarin derivatives. The chemical structures as well as relative stereochemistries of those coumarins were confirmed on the basis of extensive spectroscopic data interpretation and comparison with those previously published data. © 2013 Phytochemical Society of Europe.